The labor-market effects of service offshoring: A synthetic control approach with high-dimensional microdata - Otto Kässi (The Research Institute of the Finnish Economy (ETLA), 2022)
I use novel high-quality survey data on firms' international sourcing activities combined with firm-level financial and linked employer-employee data to study the effect of services offshoring on wages and employment. To overcome the endogeneity related to reverse causality and omitted variables, I use microsynth, a variation of the synthetic control method specially developed for high-dimensional microdata. I find that offshoring firms pay higher wages for both high-skilled and low-skilled workers, and employ fewer FTE workers compared with a synthetic control, but these effects take several years to appear.
Keywords: F14; C33; J31; 330; Service offshoring; Offshoring